Construction of Quaternary Allylic Amino Acid Derivatives through Palladium-Catalyzed Allylic Alkylation Reaction of Azlactones with Vinyl Aziridine - Huang, Ke-Xin; Chen, Zhao-Yang; Liu, Xue-Guo; Ye, Hong-Yong; Gao, Wen-Chao (Synthesis, 2022)
A highly efficient Pd-catalyzed allylic alkylation reaction of azlactones with vinyl aziridine has been achieved for the first time to access functionalized quaternary allylic amino acid derivatives (17 examples, up to 89% yield and 80% ee). Moreover, the broad scope and easy transformations of the products reinforce the value of this approach, which can enrich the chemistry of quaternary allylic amino acid derivatives.
Keywords: allylic alkylation; quaternary allylic amino acid derivatives; Pd-catalyzed; vinyl aziridine; azlactones